Laparoscopic ventral hernia repair: Results of a two thousand patients prospective multicentric database. (March 2018) - Sánchez, Luis José; Piccoli, Micaela; Ferrari, Carlo Giovanni; Cocozza, Eugenio; Cesari, Maurizio; Maida, Pietro; Iuppa, Antonio; Pavone, Giuseppe; Bencini, Lapo
Abstract: Laparoscopic incisional and ventral hernia repair (LIVHR) has been largely employed by the surgical community worldwide, despite the use of different types of mesh and fixation devices. A large nationwide prospective multicentric database collected 2005 operations from 8 high-volume centers, to investigate the perioeperative and long-term outcomes. The laparoscopic operations were completed in 1979 patients (98.7%), with a mean age of 60.7 years and a Body Mass Index of 28.8 kg/m 2 . Two hundred and one patient (18.8%) had a previous failed open repair. The average surface areas of the major defects were 47.4 and 18.2 cm 2 for postincisional and primary hernias. The mean operation time and postoperative stay were 94.4 min and s 3.7 days, respectively. We collected a total of 50 (2.5%) intraoperative and 414 (20.6%) postoperative complications, with reoperation needed in 38 cases (1.8%). After a mean follow-up period of 24 months, we recorded 62 (3.8%) confirmed recurrences. Length of surgery, hospital stay, and a previous recurrence were all risk factors for recurrence. Primary hernias had better perioperative outcomes compared to incisional hernias, except for the pain. The laparoscopic approach of both post-incisional and primary hernias seemed to be safe and feasible in short-to medium-term periods. Highlights: Laparoscopic ventral hernia repair is not accepted worldwide. Perioperative outcomes are highly jeopardized in the Literature. Postoperative complications and recurrences are very low. The laparoscopic technique could be a good option to deal with ventral hernias.